STUDENTS’ PERCEPTIONS ON SPEAKING SKILL DEVELOPMENT USING ROLE PLAY METHOD AT MA MDIA TAQWA MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2023)
In order for the students to understand what they were learning in class and be able to express their own opinions orally, the teacher must be able to motivate them to actively engage in discussion of the course materials. The ability of the teacher to use the procedures was crucial for carrying out English teaching. One of the ways in developing students’speaking skills was by giving Role Play as a form of English learning activity in the classroom. Role Play was a created situation in which students deliberatley act out or assume characters or identities they would not normally asume in order to accomplish learning goal. This study aims to find out the difficulties in speaking English encountered by students and Students’ Perceptions of the learning process. To collect the data, the researcher used mix method. The subject of the study was grade XI of MA MDIA Taqwa MakassarThe researcher made an effort to improve speech instruction, particularly by giving the students role-playing opportunities. This study was conducted in two cycles. The researcher set up a cycle of planning an action, carrying it out, and reflecting. Lesson plans, pre- and post-tests, an observation checklist, and a questionnaire were all developed by the researcher during the preparation phaseWhen putting the plan into practice, the researcher identified the pupils and looked into the issues that arise during the English learning process. When the activity of the previous cycle was deemed ineffective, the researcher then performed a reflection before moving on to the next cycle. Pre-test scores of 39%, progress scores of 59%, and post-test scores of 84% were the findings of this study. According to these findings, the pupils' speaking abilities improved.